The local thermal effect of using monopolar electrosurgery in the presence of a deep brain stimulator: Cadaveric studies on a lamb brain. (July 2019) - Geoffrey, Tipper; Ali, Taqvi Ahsan; Arvind, Singh; Ute, Pohl; HuLiang, Low
Highlights: Peri-operative guidelines for DBS patients lack clarity and have a limited evidence base. Current practice to avoid monopolar electrosurgery on DBS patients is generalised from other treatments. This work demonstrates minimal temperature rise and no thermal injury at implant sites with monopolar use. Further in vivo work may establish safe limits for monopolar electrosurgery in the presence of DBS. Abstract: In 2001, a patient with a deep brain stimulator (DBS) died following treatment with medical diathermy. Manufacturers have since advised against all forms of diathermy except bipolar electrosurgery in DBS patients. This effective ban on monopolar electrosurgery has an impact on the 150, 000 patients treated with DBS to date, a number that is set to progressively increase. Analysis of the events, technical specifications, and literature suggests that the original ban was based on extrapolation from medical diathermy to electrosurgery, two very different treatment modalities. This prompted novel work exploring the impact of electrosurgery on DBS systems. Monopolar electrosurgery was employed on an animal cadaveric model with a DBS system paired with a thermocouple at the brain implant site. Prolonged use of monopolar, including at settings higher than normal surgical practice, resulted in a maximum mean temperature increase of only 2.6 °C. Microscopic post-event analysis showed no evidence of thermal injury at the implant site. The implication is that there may be limits within which monopolar electrosurgery use is safe in patients with DBS.